2009
DOI: 10.1007/s00394-009-0777-4
|View full text |Cite
|
Sign up to set email alerts
|

Purified chickpea or lentil proteins impair VLDL metabolism and lipoprotein lipase activity in epididymal fat, but not in muscle, compared to casein, in growing rats

Abstract: The low food efficiency ratio of purified CP and L proteins related to CAS is associated with decreased plasma VLDL and adipose tissue LPL activity. The low liver TG concomitant with reduced TG and apolipoproteins contents of VLDL confirm that hypotriglyceridemia is essentially due to impaired synthesis, exportation and transport of TG by VLDL which prevent lipid storage in adipose tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
1
15
1
Order By: Relevance
“…This could be related to the higher essential amino acid content in FLT and FVHT in comparison to GLT and GVHT diets. The food efficiency ratios of faba bean diets observed here (approximately 0·33) were higher than those reported for diets containing 20 % of purified chickpea and lentil proteins (0·21) ( 36 ) . Mixed wheat–legume meals could be an effective way to improve the low nutritional performance of diets with legume protein as the sole protein source and to achieve a similar protein efficiency as a casein control diet (CD).…”
Section: Discussioncontrasting
confidence: 76%
“…This could be related to the higher essential amino acid content in FLT and FVHT in comparison to GLT and GVHT diets. The food efficiency ratios of faba bean diets observed here (approximately 0·33) were higher than those reported for diets containing 20 % of purified chickpea and lentil proteins (0·21) ( 36 ) . Mixed wheat–legume meals could be an effective way to improve the low nutritional performance of diets with legume protein as the sole protein source and to achieve a similar protein efficiency as a casein control diet (CD).…”
Section: Discussioncontrasting
confidence: 76%
“…The beneficial effects of legumes on TG levels are derived from the fibers, niacin and certain amino acid compositions of the proteins of legumes [46,49,50,51]. Addition of L -arginine could have caused disturbances in the composition of legume proteins, and the beneficial effects on TG levels mentioned above could have been eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no toxicity effects by the administration of legumes in any form were reported. However, an increase of hepatic phospholipids was induced by the administration of adzuki beans ( 41 ) , chickpeas and lentils ( 61 ) , in addition to a decrease of LPL activity in epididymal fat reported by the latter study. In addition, in the study of Shahraki et al ( 55 ) , an elevation of AST and ALT was observed in the group that consumed the aqueous extract of T. indica .…”
Section: Discussionmentioning
confidence: 74%